Modification On The Physico-Chemical Properties Of Rice Flour - Mohamad, Hanis (Universiti Sains Malaysia, 2021)
In this study, rice flour was dually-modified using a method that combined physical modification and enzyme modification, namely enzyme-debranching followed by heat-moisture treatment (HMT). For single modification, the rice flour had undergone HMT. The physicochemical properties and resistant starch content of the native and modified samples were investigated and compared. The results showed a significant reduction of amylose content along the treatment(s) used, with the native rice flour (NRF) having the highest amylose content (34.52%), followed by heat-moisture treated rice flour (HMF) (28.91%), and dual-modified rice flour (DMF) (20.82%).